Studies of the Homalomeneae (Araceae) of Peninsular Malaysia VIII: Homalomena joanneae [Chamaecladon Clade], a new locally endemic limestone-obligated species - Wong, Sin Yeng; Boyce, Peter C. (Firenze University Press, 2021)
. Homalomena joanneae is described and illustrated as a new species of the Chamaecladon Clade restricted to the industrially threatened limestone of Gunung Kanthan, Kuala Kangsar, Perak, and compared with its probable nearest congener, H. hendersonii from Kelantan.